Potential Port Site Consequences in Laparoscopic Cholecystectomy Using an Open versus Closed Approach of Pneumoperitoneum: A Comparative Study - Awni Ismail Sultan; Sami Hassoon Ali; Ozdan Akram Ghareeb (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
The standard method for cholecystectomy is laparoscopic surgery, and pneumoperitoneum can be performed in either a closed or open technique. However, exposure to the port’s consequences may enhance the patient’s morbidity. As a result, this study was carried out to compare both approaches in terms of complications at the port site of each procedure and potential risk factors. A prospective study was carried out in the department of surgery, in hospitals affiliated with Kirkuk and Diyala governorates in Iraq, from January 2019 to March 2022. The 200 patients who took part in the study were divided into two groups, each with 100 patients. The two procedures were compared for intraoperative and postoperative problems that could have arisen from port insertion up to 18 weeks. The findings showed that the highest percentage was for the following: females (84.0%), ages between 50 and 59 years (43.5%), and body mass index (BMI) range 25-30 kg/m2 (49.0%). No significant difference was observed between those variables for the two surgical techniques (p-value > 0.05). No death was recorded in the study. The following complications were observed at the port site in 10.5% of patients, with the majority reported in the open approach (8.5%): bleeding (3.0%), hematoma (2.0%), wound infection (1.5%), hernia (1.5%), and vascular injury (0.5%). Thus, we concluded that port site complications are lowest in closed laparoscopic surgery which was not shown to be statistically significant but values showed less complications. Furthermore, samples could be used to gain a good statistical significance.